2006
DOI: 10.1002/micr.20235
|View full text |Cite
|
Sign up to set email alerts
|

Repair of the main nerve trunk of the upper limb with end‐to‐side neurorrhaphy: An experimental study in rabbits

Abstract: The aim of this study was to assess the effectiveness of reinnervation using end-to-side neurorrhaphy in the upper extremity of the rabbit. The cut right ulnar nerve was repaired and sutured to the side of the median nerve about 3 cm above the elbow joint. The extent of reinnervation was quantitatively evaluated, as well as the integrity of the intact donor nerve in 36 rabbits randomly treated with fresh or delayed nerve repair with or without perineurotomy. Evaluations included nerve conduction velocity (NCV)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 23 publications
0
7
0
2
Order By: Relevance
“…Most recent studies of end-to-side neurorrhaphy have used rabbits and shown mostly satisfactory return of upper and lower limb function Zhang et al, 2006aZhang et al, , 2006b. Stamatouhou (2006) compared endto-side neurorrhaphy of the musculocutaneous nerve to the phrenic nerve using a standard neurotization technique in rabbits with satisfactory return of limb function.…”
Section: Introductionmentioning
confidence: 99%
“…Most recent studies of end-to-side neurorrhaphy have used rabbits and shown mostly satisfactory return of upper and lower limb function Zhang et al, 2006aZhang et al, , 2006b. Stamatouhou (2006) compared endto-side neurorrhaphy of the musculocutaneous nerve to the phrenic nerve using a standard neurotization technique in rabbits with satisfactory return of limb function.…”
Section: Introductionmentioning
confidence: 99%
“…34 The number of regenerating axons may be proportional to the CMAP amplitude, but the CMAP amplitude may not be strictly proportional to functional motor recovery. 35 These findings suggest that the maximal degree of reinnervation is achieved 12 weeks after ETE neurorrhaphy, while more time should be given for further reinnervation after ETS neurorrhaphy. On the other side, although the diameters of sprouting axons were smaller than those in the control group and contralateral sides, there is no significant difference between the diameters of the myelinated axons distal to the ETE and ETS coaptation sites.…”
Section: Discussionmentioning
confidence: 80%
“…9 Most of the experimental studies concluded that the results were encouraging with axonal nerve regeneration. 3 Samal et al 18 found a comparable capacity of both intact sensory and motor axons to send collateral sprouts into a denervated nerve stump. Sananpanich et al, 4 comparing end-to-end with end-to-side neurorrhaphy, found that only a few donor nerve motor and sensory axons contribute to reinnervation in the case of end-to-side nerve repair compared with end-to-end repair.…”
Section: Discussionmentioning
confidence: 97%